THE EFFECTS OF INQUIRY LEARNING MODEL TRAINING AND CRITICAL THINKING TOWARDS SMA STUDENT LEARNING OUTCOMES - Ella Lady Saura; Betty M. Turnip (Jurnal Pendidikan Fisika, 2014)
The purposes of the research are: (1) To determine differences in learning outcomes of students with Inquiry Training models and Direct Instruction teaching models, (2) to determine differences in physics learning outcomes of students who have high critical thinking and low critical thinking, (3) to determine the interaction between learning models with the level of critical thinking in improving student Physics learning outcomes. The sample in this study conducted in a cluster random sampling of two classes, where the first class as a class experiment applied Inquiry Training models as a class and the second class of controls implemented Direct Instruction models. The instrument is used in this study is physics learning outcomes tests in narrative form as many as 7 questions and critical thinking test in narrative form as 7 questions that have been declared valid and reliable. The results were found: (1) there are differences in physical students learning outcomes are taught by Inquiry Training models and Direct Instruction teaching models. Learning outcomes of students who are taught by Inquiry Learning Model Training better than student learning outcomes are taught with Direct Instruction Model Learning. (2) There is a difference in student's learning outcomes that have high critical thinking and low critical thinking. Student learning outcomes that have a high critical thinking better than student learning outcomes that have a low critical thinking. (3) There is interaction between learning and mastery of material Model Physics prerequisite to student learning outcomes. Learning outcomes of students who are taught by the model is influenced also by the Inquiry Training critical thinking, while learning outcomes of students who are taught with Direct Instruction models are not affected by the students' critical thinking.